Sedimentary n?alkane biomarkers with carbon, nitrogen and δ^1^3C profiling from the Baldwin Peninsula (Arctic Alaska) - Fabian Seemann; Carolin Frauhammer; Lars Ebel; Justin Lindemann; Mikaela Weiner; Juliane Wolter; Jens Strauss (PANGAEA, 2025)
In March 2024, sediment cores were collected along two land–ocean transects on the Baldwin Peninsula, Alaska, encompassing permafrost uplands, thermokarst lakes, drained lake basins, and nearshore marine sites. Transect 0 (T0) includes a recently drained lake basin (drainage in 2022), whereas Transect 1 (T1) represents a semi-drained lake basin. These transects capture characteristic landscape dynamics of the region and their implications for organic matter transformation, with both transects hosting taliks. To assess organic carbon properties, n-alkane biomarkers were analyzed. Raw chromatographic data were processed with XCalibur (Thermo Fisher), and derived proxies were subsequently calculated.